3b^8*49p^5/7p^3*9b the answer is 7b^7p^2/3 but how is the problem worked out to get the answer

You can also look at this equation as the multiplication of two fractions:

1. 3b^{8} * 49p^{5} / 7p^{3} * 9b is the same as
(3b^{8}_{/9b}) *
(49p^{5}_{/7p3})

2. Now lets simplify the fractions before multiplying them together:

a. 3b^{8}_{/9b}

= b^{8}/_{3b}

= b^{8-1}_{/3}

= b^{7}_{/3}

b. 49p^{5}_{/7p3}

= 7p^{5}_{/p3}

= 7p^{5-3}

= 7p^{2}

**
**3. Lastly complete the multiplication --> b

^{7}

_{/3}* 7p

^{2 }which is 7b

^{7}p

^{2}

_{/3}

** **